2015
DOI: 10.1111/apa.13205
|View full text |Cite
|
Sign up to set email alerts
|

Some neonatal risk factors for adult pulmonary arterial hypertension remain unknown

Abstract: By adjusting for factors linked to adult pulmonary hypertension, namely congenital heart defects, pulmonary diseases and premature birth, we were able to show that other unknown factors may influence the risk for pulmonary hypertension among adults who were born premature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 33 publications
(38 reference statements)
0
34
1
Order By: Relevance
“…However, a recent Swedish registry review of adults with PAH identified premature birth as an independent risk factor for the development of adult onset PAH. 108 It is highly probable that additional, currently unrecognized, perinatal and developmental factors also affect late development of PH.
Fig.
…”
Section: Long-term Implications For Early Diagnosis and Treatment Of mentioning
confidence: 99%
“…However, a recent Swedish registry review of adults with PAH identified premature birth as an independent risk factor for the development of adult onset PAH. 108 It is highly probable that additional, currently unrecognized, perinatal and developmental factors also affect late development of PH.
Fig.
…”
Section: Long-term Implications For Early Diagnosis and Treatment Of mentioning
confidence: 99%
“…Infants born in different eras of neonatology show similar long‐term impairment in lung function, airway obstruction, structural abnormalities of the gas transfer and pulmonary function . However, in a recent study we found that premature birth in the pre‐surfactant era was associated with an increased risk of adult PH even after adjustments were made for these risk factors . Our working hypothesis was that PH was associated with premature birth also in the post‐surfactant era.…”
Section: Introductionmentioning
confidence: 81%
“…In a previous study, we found an increased risk of PH in adults born preterm . This study covered mainly the 1970s and 1980s, which was a period when surfactant was not in regular clinical use and is called the “pre‐surfactant era.” The first successful trial of endotracheal surfactant administration to preterm infants was performed in the 1980s and surfactant treatment was later proven to reduce the need for supplemental oxygen and ventilator support as well as the risk of neonatal death.…”
Section: Discussionmentioning
confidence: 99%
“…Long term, preterm birth is associated with an 8.5‐fold increased risk for developing pulmonary hypertension (defined as a mean pulmonary artery pressure ≥25 mmHg) in childhood and adolescence, and a 3.1‐fold increased risk in adulthood, even after adjusting for confounding factors such as acute pulmonary disorders, congenital heart defects, congenital diaphragmatic hernia and chromosomal disorders (Naumburg et al . , ). At rest, otherwise healthy young adults born preterm exhibit increased vascular stiffness with elevations in resting mean pulmonary arterial pressure (Goss et al .…”
Section: Impaired Pulmonary Vascularizationmentioning
confidence: 99%